Not Yet Game Over: A Reappraisal of Video Game Addiction - Jhee, Jiow Hee; Lye, Qin Ting; Woo, Kenneth (Loading)

(untitled) (Canadian Game Studies Association, 2019)
The rapid expansion of video gaming in an internet-using society has brought on a renewed focus on the phenomenon of video game addiction. Despite this focus, there remains a crucial absence of consensus over the diagnostic criteria of video game addiction. Currently both psychological and behavioral interventions regard screen time as an indicator of video game addiction. However, these interventions are challenged by substantial literature that increasingly regard time to not be a predictor of addiction. To build onto the work that has been done, this paper argues that time is an inadequate criterion in which to ascertain video game addiction, proposing that a physiological-based criteria be used in conjunction with contextualized understandings of video game dynamics to approach video game addiction. This realignment is all the more pressing as video games begin a transition from a leisure activity to its current orientation as a viable career option.